Murder in the museum : a Fathering mystery - Brett, Simon (London : Pan Books, 2004)
Home Office retiree Carole Seddon investigates the discovery of a long-buried skeleton in the yard of a literary museum, which could blacken the good name of late poet Esmond Chadleight, especially with an eager American biographer trolling the grounds.
Keywords: Seddon, Carole (Fictitious chracter) -- Fiction; Friendship -- Fiction; Jude (Fictatious chracher) -- Fiction; Women detectives -- England -- Fiction